2019
DOI: 10.1111/hel.12584
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Would susceptibility‐guided treatment achieve acceptable cure rates for second‐line Helicobacter pylori therapy as currently practiced?

Abstract: Background Susceptibility‐guided treatment has been proposed as a way to improve Helicobacter pylori eradication rates. Evidence on its efficacy for rescue therapy is very scarce. The aim of this study was to indirectly assess the applicability and effectiveness of susceptibility‐guided treatment by evaluating (a) the rate of acceptance of endoscopy, (b) its success in detecting resistances, and (c) infection cure rates in patients harboring strains found to be susceptible to the antibiotics administered in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…In the absence of a national registry other regional centres in the United States could consider a similar review of their available data to provide comparisons across regions, in order to help facilitate antibiotic therapy for refractory HP. Routine culture has so far not been recommended, as it is not clearly beneficial over empirical rescue therapy . Even in our study, given that culture rate was approximately 70%, many patients would undergo an endoscopy without subsequent culture results, and culture is certainly an imperfect test.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In the absence of a national registry other regional centres in the United States could consider a similar review of their available data to provide comparisons across regions, in order to help facilitate antibiotic therapy for refractory HP. Routine culture has so far not been recommended, as it is not clearly beneficial over empirical rescue therapy . Even in our study, given that culture rate was approximately 70%, many patients would undergo an endoscopy without subsequent culture results, and culture is certainly an imperfect test.…”
Section: Discussionmentioning
confidence: 65%
“…Routine culture has so far not been recommended, as it is not clearly beneficial over empirical rescue therapy. [26][27][28] Even in our study, given that culture rate was approximately 70%, many patients would undergo an endoscopy without subsequent culture results, and culture is certainly an imperfect test. Future studies should evaluate its role in guiding treatment and subsequently decreasing future antibiotic courses and therefore antibiotic resistance.…”
Section: Discussionmentioning
confidence: 67%
“…A German study looked at real-time genotypic clarithromycin and/or levofloxacin susceptibility as tested by PCR analysis of 144 H pylori-positive strains from patients with prior treatment failure. 35 From a first-line perspective in an area of high antibiotic resistance in South Korea, eradication rates of 93% were obtained for culture-based therapy. More encouraging results were obtained in a large, multicenter open-label trial of 450 patients who had failed two previous treatment regimes where genotypic resistance tailored treatment led to 78% eradication, but in this case empirical quadruple sequential therapy with a cure rate of 71% was an acceptable alternative after consideration of accessibility, cost, and patient preference.…”
Section: Suscep Tib Ilit Y-g Uided Ther Apymentioning
confidence: 99%
“…34 A systematic review of 36 eligible studies on this topic, including 2890 patients, indicated a cure rate of 72% in the patients harboring clarithromycin-susceptible strains after previous clarithromycin treatment, 93% in the metronidazole-susceptible strains, and 84% in the levofloxacin-susceptible strains. 35 From a first-line perspective in an area of high antibiotic resistance in South Korea, eradication rates of 93% were obtained for culture-based therapy. 32 Separately, a study from China compared eradication rates for first-line susceptibility-guided treatment with bismuth-based quadruple therapy and found excellent eradication rates for both regimes, 92% and 85%, respectively.…”
Section: Suscep Tib Ilit Y-g Uided Ther Apymentioning
confidence: 99%
“…Although susceptibility‐guided treatment has been proposed as a way to improve H pylori eradication rates, evidence on its efficacy for rescue therapy is very scarce. A recent systematic review found that susceptibility‐guided treatment alone did not achieve adequate cure rates for second‐line rescue therapies . Another systematic review concluded that, for third‐line therapy, performing culture is associated with cure rates which are, at best, moderate and this approach has never been compared with a well‐devised empirical therapy .…”
mentioning
confidence: 99%